The variation of breast milk composition during the lactation stage for mothers from the Csík region - Salamon, Szidónia; Salamon, Rozália Veronika; Csapó, János (Acta Agraria Debreceniensis, 2010)
The aim of our research was the examination of breast-milk composition from mothers living in the Csík region and to follow their milk composition variations during lactation. In this article we present the results obtained from three mothers, paying particular attention to essential components. The breast milk samples were collected from healthy mothers with similar habits and age. The milk samples were collected with a hand pump at the same time after the feeding. The sampling period was from day 5 to the 14th weeks of lactation. The nutrition of mothers was recorded on a questionnaire, completed by the mothers themselves. Comparing our experimental results with data in the literature it was concluded that the milk protein content was very similar to the milk of mothers from other European countries, and is decreased during lactation. The total saturated fatty acid content was lower, but the palmitic acid content was slightly higher. Regarding the essential fatty acid composition the linoleic- and the arachidonic acid contents were appropriate from a nutritional point of view. The linolenic acid was present in lower amounts, but the docosahexanoic acid was almost undetectable. The iron and manganese contents were in good agreemen with published results, but the zinc content of the breast milk was lower and its copper content was higher. These differences in milk composition can be explained by the different nutritional habits of our subjects.